Нужно упростить. Не тупо перемножая, но подробно ( a - 1 ) * ( a^9 + a^8 + a^7 + a^6 + a^5 + a^4 + a^3 + a^2+ a + 1 ) + 1
Нужно упростить. Не тупо перемножая, но подробно
( a - 1 ) * ( a^9 + a^8 + a^7 + a^6 + a^5 + a^4 + a^3 + a^2+ a + 1 ) + 1
Ответ(ы) на вопрос:
Есть формула:
[latex]a^n-b^n = (a-b)(a^{n-1}+a^{n-2}b+...+ab^{n-2}+b^{n-1})[/latex]
В данном случае:
[latex]a^{10} - 1 = (a-1)(a^9+a^8+...+a+1) [/latex]
[latex]( a - 1 )(a^9 + a^8 + a^7 + a^6 + a^5 + a^4 + a^3 + a^2+ a + 1 ) + 1 [/latex][latex]= a^{10}-1+1=a^{10}[/latex]
Не нашли ответ?
Похожие вопросы